Dinamika Persatuan Islam Tionghoa Indonesia NTB dalam Interaksi Sosial Dagang di Tengah Komunitas Warga Kota Mataram - Muzakir Muzakir; Fahrurrozi Fahrurrozi; Mohammad Fakhri (TAMADDUN: Jurnal Ilmu Sosial, Seni, dan Humaniora, 2026)
This study aims to analyze the dynamics of the Indonesian Chinese Muslim Association (PITI) of West Nusa Tenggara in social interactions and trading activities within the community of Mataram City. A qualitative approach was employed using observation and in-depth interviews with PITI members and local residents. The data were analyzed descriptively to identify communication patterns, cultural acculturation processes, and factors influencing social interaction. The findings reveal that PITI members actively contribute to fostering harmonious social relations through economic activities and intercultural communication. These interactions encourage acculturation and assimilation processes between Chinese Muslim communities and other ethnic and religious groups. Linguistic diversity, mutual respect, and effective communication skills were found to be key factors in strengthening social cohesion and shaping an inclusive cultural identity in Mataram City. The study highlights the role of intercultural communication in promoting social integration and sustainable community development in a multicultural society.